Extra-legal steadying factors' in the Article 267 TFEU preliminary reference procedure - Cotter, John (Trinity College (Dublin, Ireland). School of Law, 2017)
This dissertation presents the thesis that there are 'extra-legal steadying factors' in the EU legal system and the preliminary reference procedure that serve to reduce significantly the impact of obstacles to 'legal certainty', or put differently, promote 'reckonability' in the Article 267 TFEU procedure. In advancing this thesis, the dissertation utilises the theories of Llewellyn in The Common Law Tradition: Deciding Appeals (1960), devised in the context of American appellate courts. Llewellyn's fourteen 'steadying factors' are categorised, consistent with existing scholarship, as 'legal' (the normative character of 'legal doctrine' and 'known doctrinal techniques') and 'extra legal'. The dissertation focusses on the role of the latter in preliminary references, and sub-categorises them as 'internal', 'external' and 'procedural'. The dissertation also emphasises, as an important result of the thesis, that Llewellyn's 'steadying factors', or at least those examined herein, are capable of application outside of the American appellate court context (the 'applicability by-product').
Embargo End Date: 2023-03-21
Keywords: Law, Ph.D.; Ph.D. Trinity College Dublin, 2017